Conserving small natural features with large ecological roles: A synthetic overview. (July 2017) - Hunter, Malcolm L.; Acuña, Vicenç; Bauer, Dana Marie; Bell, Kathleen P.; Calhoun, Aram J.K.; Felipe-Lucia, María R.; Fitzsimons, James A.; González, Eduardo; Kinnison, Michael; Lindenmayer, David; Lundquist, Carolyn J.; Medellin, Rodrigo A.; et al.
Abstract: Small Natural Features (SNFs) are analogous to keystone species in that they have ecological importance that is disproportionate to their size. Thus the recognition and management of SNFs can be an efficient way to conserve biodiversity and ecosystem services. In particular, while the size of SNFs can engender threats (e.g., they are often overlooked and are relatively vulnerable to complete destruction), small size also leads to special conservation opportunities (e.g., integration with resource uses such as forestry or fisheries). Commonly, SNF conservation begins with education and inventory to form a foundation for appropriate, targeted protection and/or sustainable management. However, in cases of severe degradation or loss, more intensive activities such as restoration or creation may be required. Diverse approaches to conservation action are possible. For example, sometimes SNF conservation is undertaken incidentally to other efforts or on a voluntary basis; sometimes it involves substantial economic incentives or restrictive regulations. In general, the required investment for SNF conservation is likely to be smaller than that for larger areas, with disproportionate benefits given the substantial spatio-temporal influence of these features. In practice, conservation of SNFs should be complementary to traditional, larger-scale, forms of conservation by fostering creative, constructive efforts to conserve some seemingly minor features; features that have previously unknown or unappreciated roles critical to their broader ecosystems and to biodiversity. Graphical abstract: Highlights: Small Natural Features (SNF) have large ecological importance relative to their size. SNF importance is shaped by spatio-temporal context. Examples of SNFs include desert springs, bat caves, temporary pools, and coral heads. SNFs management represents both novel challenges and opportunities. SNFs can be conserved in concert with traditional land use activities.